Discrimination in the Small-Business Credit Market - Blanchflower, David G.; Levine, Phillip B.; Zimmerman, David J. (The Review of Economics and Statistics, 2003)
We use data from the 1993 and 1998 National Surveys of Small Business Finances to examine the existence of racial discrimination in the small-business credit market. We conduct an econometric analysis of loan outcomes by race and find that black-owned small businesses are about twice as likely to be denied credit even after controlling for differences in creditworthiness and other factors. A series of specification checks indicates that this gap is unlikely to be explained by omitted variable bias. These results indicate that the racial disparity in credit availability is likely caused by discrimination.